The Role of the Gastrointestinal Mucus System in Intestinal Homeostasis: Implications for Neurological Disorders - Herath, Madushani; Hosie, Suzanne; Bornstein, Joel C.; Franks, Ashley E.; Hill-Yardin, Elisa L. (Frontiers in Cellular and Infection Microbiology, 2020)
Mucus is integral to gut health and its properties may be affected in neurological disease. The mucus lining of the gastrointestinal (GI) tract plays a prominent role in physically preventing microbial content reaching the intestinal epithelium. Multiple factors influence the volume, viscosity, porosity and microbial content of mucus in the GI tract, including the proliferation of mucus-secreting goblet cells from stem cells located at the base of GI crypts. Via a number of mechanisms, abnormalities in neuronal networks occurring in neurological disorders may alter the structure and function of mucus in patients. The gut has its own intrinsic neuronal network, the enteric nervous system, which extends the length of the GI tract and innervates the mucosal epithelium. The GI tract and commensal microbiota influence mood and behavior via neural and non-neural pathways within the gut-brain axis. Both dysbiosis and gut dysfunction are commonly reported in several neurological disorders such as Parkinson’s and Alzheimer’s disease as well in patients with neurodevelopmental disorders including autism. Since some microbes use mucus as a prominent energy source, changes in mucus properties could alter, and even exacerbate, dysbiosis-related gut symptoms in neurological disorders. This review summarizes existing knowledge of the structure and function of the mucus of the GI tract and highlights areas to be addressed in future research to better understand how intestinal homeostasis is impacted in neurological disorders.